Граничні цикли подвійного маятника з жорсткими характеристиками пружних елементів і слідкуючою силою - Ічанський, В.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
It is shown that the stable and unstable limit cycles exist in the phase space of а double pendulum with the hard characteristic of elastic elements.